The convergence of Nahdlatul Ulama and Jamaah Tabligh traditions in Temboro Village, Magetan, East Java - Nurhayati, Anifa; Imam Muhsin; Prabowo, Thoriq Tri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
Temboro Village in East Java, known as the